Spitzer observations of gj 3470 b: a very low-density neptune-size planet orbiting a metal-rich m dwarf* - Demory, Brice-Olivier; Torres, Guillermo; Neves, V.; Rogers, Leslie A.; Gillon, Michaël; Horch, Elliott P.; Sullivan, Peter W.; Bonfils, Xavier; Delfosse, Xavier; Forveille, Thierry; Lovis, Christophe; Mayor, Michel; et al. (The Astrophysical Journal, 2013)
We present Spitzer/IRAC 4.5 μm transit photometry of GJ 3470 b, a Neptune-size planet orbiting an M1.5 dwarf star with a 3.3 day period recently discovered in the course of the HARPS M-dwarf survey. We refine the stellar parameters by employing purely empirical mass-luminosity and surface brightness relations constrained by our updated value for the mean stellar density, and additional information from new near-infrared spectroscopic observations. We derive a stellar mass of and a radius of of M* = 0.539 +0.047-0.043 M⊙ and a radius of R* = 0.568+0.037-0.031 R⊙. We determine the host star of GJ 3470 b to be metal-rich, with a metallicity of [Fe/H] = +0.20 ± 0.10 and an effective temperature of Teff = 3600 ± 100 K. The revised stellar parameters yield a planetary radius Rp= 4.83+0.22-0.21 R⊕that is 13% larger than the value previously reported in the literature. We find a planetary mass M p= 13.9+1.5-1.4 M⊕ that translates to a very low planetary density, ρp = 0.72+0.13 -0.12 g cm-3, which is 33% smaller than the original value. With a mean density half of that of GJ 436 b, GJ 3470 b is an example of a very low-density low-mass planet, similar to Kepler-11 d, Kepler-11 e, and Kepler-18 c, but orbiting a much brighter nearby star that is more conducive to follow-up studies. © 2013. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; planetary systems; stars: individual (GJ 3470); techniques: photometric; techniques: spectroscopic

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed